Percepção dos gestores sobre as concepções de tecnologia presentes nas indústrias brasileiras de baixa, media-baixa e media-alta tecnologia - Moraes, Jessyca (2017)
The objective of this work is to identify the managers' perception about the technology conceptions present in the low, medium-low and medium-high technology industries. This study is about sociotechnical analysis that was carried out in productive environments. The data collection was carried out to determine the profile of the workers regarding the conceptions of technology found in the industry. For the final application that aimed to identify the managers' perception about the technology conceptions present in the industries, the low, medium-low and medium-high technology segments were used. In the application of the instrument, 84 questionnaires were collected, of which 80 were validated. Regarding the technology level 67.50% are inserted in the medium-low-tech industries 12.50% of respondents from low-tech industries and from medium-high technology industries 20% of respondents were registered. The total Cronbach's α of the instrument in this sample is satisfactory, considering that result was 0.780. Discriminant analysis and the Anova test were performed, considering ρ-value <0.05 to have a significant difference between at least one of the groups. For the analysis performed between the constructs of the test was found ρ-value≤0.001, that is, there is a difference between the means of at least one of the constructs. Therefore, the questionnaire is valid because it does not evaluate the same points in different constructs. It became possible in a more in-depth assessment to identify the managers' perception of industrial technological innovation. To do so, we took into account the tests obtained from the answers that point out that for the most part the perception is that the technology assists in the development of their work. It was obtained that the most important conceptions were technological appropriation and the utilitarian conception of technology.